The Case of Сushing Syndrome in a Child of 15 Years after Prolonged Endonasal Use of Dexamethasone - S. S. Postnikov; M. E. Karmanov; E. V. Kuvaldina; A. Z. Gadzhieva; M. N. Kostyleva; A. N. Gratsianskaya; A. E. Ermilin (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Abstract. The article describes the case of drug Cushing syndrome as a result of prolonged (for 10 months) endonasal use of dexamethasone and oxymetazoline mixture, which was prepared by the patient's mother. Medical control was absent. The content of dexamethasone in the vial and the concentration of oxymetazoline was not known. During the examination, in addition to Cushing syndrome, an atrophy of the nasal mucosa as a second side effect was revealed. Thus, in the above case, there were two complications of incorrect using of drugs - local and systemic.